Dispelling Potential Fears Associated with Stem Cell Donation - Anagnostopoulos, Alexander E.; Baribeau, Owen; Guo, Yujia (Julia); Lee, Anna; Luo, Owen Dan (The Meducator, 2018)
An increasing number of patients require life-saving stem cell transplants, often from unrelated donors. In order to facilitate this process, bone marrow and stem cell registries have been established to genetically catalog potential donors and can be used to find matches for patients in need. Given the wide genetic variability in populations and significant ethnic disparities in donor registries worldwide, there are substantial gaps in the availability of compatible unrelated stem cell donors. Limited understanding of the procedures involved in stem cell donation, along with potential misconceptions of associated risks, may discourage prospective donors. Many people are unaware that there are two established methods for stem cell donation from adult donors, either through bone marrow harvest or—more commonly— through peripheral blood stem cell harvest. This evidence-based commentary explores these two procedures, deconstructs misconstrued fears associated with stem cell donation, and subsequently encourages readers to consider registering as stem cell donors.